Clinicopathological Analysis of Anterior-Superior Mediastinal Masses - Priyadarshini, Sarah Grace; Alavandar, Ezhilvizhi (Annals of Pathology and Laboratory Medicine, 2021)
Background: The mediastinum is the space between the two lungs, bounded anteriorly by the sternum and posteriorly by the vertebral column. A spectrum of neoplastic and non-neoplastic lesions can arise in the mediastinum. Methods: A total of 14 cases were retrospectively retrieved from the Histopathology department. The cases had histopathological diagnosis either in image guided, thorocoscopic, transbronchial or excision biopsies. Results: The majority of cases (43% n=6) were of thymic origin, which included both neoplastic lesions of thymoma group and non-neoplastic lesion like thymic cysts. The thymoma group included 3 cases of thymoma B3 and 1 case of thymoma AB. The lymphoid lesions include Hodgkin lymphoma (14.3%; n=2) and non-Hodgkin lymphoma (7.1%; n=1). The mesenchymal lesions (21.4%; n=3) included lipoma, solitary fibrous tumor and schwannoma which accounts for one case each. A rare case of ectopic parathyroid adenoma (7.1%; n=1). and a case of metastatic papillary carcinoma (7.1%; n=1) were also reported. Conclusion: The diagnosis of mediastinal mass lesions can pose difficulties due to its wide clinicopathologic spectrum to the clinician, radiologists and pathologist. A multimodal approach with histopathological examination and immunohistochemistry can help in arriving at an accurate diagnosis.